A Woman’s Perspective on Circassian folk culture: Results of an Interview - Mahmut Delen (Şarkiyat Mecmuası)
The Circassians are considered one of the deep-rooted peoples of the Caucasus and have a unique culture. With a history of approximately one hundred and fifty years in Anatolia, the Circassians are characterized by their adherence to their traditions, hospitality and folk culture, which is evident in every aspect of their lives. The Circassians have managed to pass on their cultural heritage to future generations despite the many social rifts and traumas they have experienced. Circassian women have the greatest role in transmitting folk culture. The research attempted to gather data on the daily lives of Circassian women, the division of roles among them, and their impact on the transmission of culture through an interview with a woman who lives in Tekneli, a Circassian village in the central district of Tokat province, and who has continued to practice Circassian culture throughout her life. Based on the data obtained using the in-depth interview method through a semi-structured interview form, analyses were conducted on the perception of women in the Circassian culture. The categories and codes that emerged from the analyses were treated separately and an attempt was made to make sense of them. According to the results of the research, it has been evaluated that much of the common information about Circassian women in the society contains misinformation and that women are given great importance, although there is a patriarchal way of life in the Circassian society.